Peran Badan Pengawas Pemilihan Umum (Bawaslu) Provinsi Kalimantan Tengah dalam Menangani Pelanggaran Administrasi Pemilu - Siti Wahidah; Lia Husnul Hatimah; Tamara Maya Devitri; Ahmad Fajri; Aris Sunandar Suradilaga; Tohirokhi Minallah (Nusantara Mengabdi Kepada Negeri, 2025)
This paper aims to provide knowledge about the role of the General Election Supervisory Body (Bawaslu) in handling administrative election violations. Bawaslu, as an independent institution, has the main task of supervising all stages of the general election and ensuring that its implementation runs in accordance with applicable legal provisions. Administrative election violations, which include actions that are not in accordance with administrative election regulations, are one of the main focuses of Bawaslu's supervision. Handling these administrative violations is very important to maintain the integrity of the election and public trust in the democratic process. Handling administrative election violations by Bawaslu, from the prevention stage to enforcement. In addition, various challenges faced by Bawaslu in carrying out its role are also described, such as limited human resources and supporting facilities, as well as the complexity of administrative violation cases. As a result, the role of Bawaslu in handling administrative election violations is very important in maintaining election participants' compliance with the rules, although there are still several obstacles that affect the effectiveness of the implementation of this supervision. Therefore, increasing capacity and cross-institutional cooperation is crucial to strengthening Bawaslu's supervisory function in the future.